Effect of tetracycline hydrochloride application on dental pulp stem cell metabolism–booster or obstacle for tissue engineering? - Wang, Wang; Sun, Jiangling; Aarabi, Ghazal; Peters, Ulrike; Fischer, Frank; Klatt, Jan; Gosau, Martin; Smeets, Ralf; Beikler, Thomas (Frontiers in Pharmacology, 2023)
Stem cells and scaffolds are an important foundation and starting point for tissue engineering. Human dental pulp stem cells (DPSC) are mesenchymal stem cells with self-renewal and multi-directional differentiation potential, and are ideal candidates for tissue engineering due to their excellent biological properties and accessibility without causing major trauma at the donor site. Tetracycline hydrochloride (TCH), a broad-spectrum antibiotic, has been widely used in recent years for the synthesis of cellular scaffolds to reduce the incidence of postoperative infections. In order to evaluate the effects of TCH on DPSC, the metabolism of DPSC in different concentrations of TCH environment was tested. Moreover, cell morphology, survival rates, proliferation rates, cell migration rates and differentiation abilities of DPSC at TCH concentrations of 0-500 μg/ml were measured. Phalloidin staining, live-dead staining, MTS assay, cell scratch assay and real-time PCR techniques were used to detect the changes in DPSC under varies TCH concentrations. At TCH concentrations higher than 250 μg/ml, DPSC cells were sequestered, the proportion of dead cells increased, and the cell proliferation capacity and cell migration capacity decreased. The osteogenic and adipogenic differentiation abilities of DPSC, however, were already inhibited at TCH con-centrations higher than 50 μg/ml. Here, the expression of the osteogenic genes, runt-related transcription factor 2 (RUNX2) and osteocalcin (OCN), the lipogenic genes lipase (LPL), as well as the peroxisome proliferator-activated receptor-γ (PPAR-γ) expression were found to be down-regulated. The results of the study indicated that TCH in concentrations above 50µg/ml negatively affects the differentiation capability of DPSC. In addition, TCH at concentrations above 250µg/ml adversely affects the growth status, percentage of living cells, proliferation and migration ability of cells.